Evaluation of Utilization of Information Systems in Jambi University Perspective Human Organization Technology (Hot) – Fit Framework - Yuliusman; Putra, Wirmie Eka; Setiawan, Dedy; Indrawijaya, Sigit; Jaya, Indra; Fitri, Lucky Enggrani (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research was to be able to prove empirically the Human Organization Technology (HOT) - a FIT framework for evaluating the application of information systems toward systems that have implemented in university, especially at Jambi University. The type of data used in this study was primary data obtained directly from respondents using a list of statements in the form of a questionnaire. The research sample of this study was students in Jambi University. To calculate the determination of the number of samples, we used the sampling method to use the Slovin formula by using a 5% error level. The total example of this study was 400 people. The methodology of Data analysis carried out by using the Structural Equation Modeling technique (SEM) and SmartPLS tools. The finding in this study found that the dimensions of system quality in the technology aspect did not affect the utilizing, usage satisfaction, and structure and dimensions of information quality. The dimensions of service quality from the technological issue did not change the dimensions of organizational structure from the regulatory aspect. For the dimensions of user satisfaction from the human element, the dimensions of the organizational structure from the corporate issue also did not affect the net benefits. While other hypotheses such as information quality dimensions, service quality dimensions, system usage dimensions affected the proportions of user satisfaction, for the information quality dimension, the dimensions of service quality from the technology aspect affected the use of the system from the human element. Likewise, the system usage dimension influenced the dimensions of user satisfaction, and the environmental size changed net benefits. SIAKAD was a mandatory system, so that technology, especially system quality, was not necessary for evaluating the success of an order, the important thing was the quality of information and the quality of service to human and organizational aspects.